2008
DOI: 10.1074/jbc.m802069200
|View full text |Cite
|
Sign up to set email alerts
|

The PDZ Protein Mupp1 Promotes Gi Coupling and Signaling of the Mt1 Melatonin Receptor

Abstract: The concept of organized networks has emerged in the field of cellular signaling in the last few years. Assembling the different partners in close proximity optimizes the spatial and temporal organization and the specificity of the cellular response. The assembly of these multimolecular complexes occurs through the interaction of modular domains recognizing their target counterparts. PDZ domains are widely spread modules exhibiting this function. Data bank exploration with SMART (1) identifies 584 PDZ domains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 56 publications
(72 reference statements)
6
57
0
Order By: Relevance
“…In agreement with these previous studies, here we found that in cultured cortical neurons, 5-HT 2A receptors colocalize with both PSD-95 and MUPP1 in the dendrites and dendritic spines of cortical pyramidal neurons, and when coexpressed in COS-7 cells, MUPP1 facilitates the membrane targeting of 5-HT 2A receptors which can be prevented by mutating the receptor PDZ binding motif. Importantly, MUPP1 is a scaffold for a growing list of synaptic proteins that are involved in GPCR and small GTPase signaling (27,(39)(40)(41). Our data, along with previous studies, are consistent with the roles of both MUPP1 and PSD-95 as protein scaffolds that may integrate signals through GPCRs at the synapse, provide avenues for crosstalk between signaling pathways, and function in the membrane localization of some receptors and signaling proteins.…”
Section: Discussionsupporting
confidence: 77%
“…In agreement with these previous studies, here we found that in cultured cortical neurons, 5-HT 2A receptors colocalize with both PSD-95 and MUPP1 in the dendrites and dendritic spines of cortical pyramidal neurons, and when coexpressed in COS-7 cells, MUPP1 facilitates the membrane targeting of 5-HT 2A receptors which can be prevented by mutating the receptor PDZ binding motif. Importantly, MUPP1 is a scaffold for a growing list of synaptic proteins that are involved in GPCR and small GTPase signaling (27,(39)(40)(41). Our data, along with previous studies, are consistent with the roles of both MUPP1 and PSD-95 as protein scaffolds that may integrate signals through GPCRs at the synapse, provide avenues for crosstalk between signaling pathways, and function in the membrane localization of some receptors and signaling proteins.…”
Section: Discussionsupporting
confidence: 77%
“…Second, MAGI-2 overexpression was found to have no effect on ␤ 1 AR-mediated cAMP signaling and to promote agonist-induced ␤ 1 AR internalization (40), but it was found to reduce vasoactive intestinal polypeptide type-1 receptor-mediated cAMP signaling and suppress agonist-induced receptor internalization (41). Finally, although MUPP1 enhances GABA B receptor signaling, it functions to uncouple the melatonin-1 receptor from G␣ i (42,43). Similarly, this study demonstrates that SAP97 regulates CRFR1 trafficking, because overexpression of GFP-SAP97 prevents CRFR1 endocytosis and knockdown of endogenous SAP97 promotes CRFR1 endocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…125 I]iodomelatonin as described previously (15). Receptors were solubilized with 1% digitonin and precipitated with a mixture of three anti-5-HT 2C rabbit antibodies (18461-10656, 18461-10657, and 18003-42961, Genway) or a pool of control preimmune serum, and immunoprecipitated radioactivity was determined.…”
Section: Methodsmentioning
confidence: 99%